Subthreshold nitric oxide synthase inhibition improves synergistic effects of subthreshold MMP‐2/MLCK‐mediated cardiomyocyte protection from hypoxic injury. Issue 6 (17th March 2016) - Bil‐Lula, Iwona; Lin, Han‐Bin; Biały, Dariusz; Wawrzyńska, Magdalena; Diebel, Lucas; Sawicka, Jolanta; Woźniak, Mieczyslaw; Sawicki, Grzegorz
Abstract: Injury of myocardium during ischaemia/reperfusion (I/R) is a complex and multifactorial process involving uncontrolled protein phosphorylation, nitration/nitrosylation by increased production of nitric oxide and accelerated contractile protein degradation by matrix metalloproteinase‐2 (MMP‐2). It has been shown that simultaneous inhibition of MMP‐2 with doxycycline (Doxy) and myosin light chain kinase (MLCK) with ML‐7 at subthreshold concentrations protects the heart from contractile dysfunction triggered by I/R in a synergistic manner. In this study, we showed that additional co‐administration of nitric oxide synthase (NOS) inhibitor (1400W or L‐NAME) in subthreshold concentrations improves this synergistic protection in the model of hypoxia–reoxygenation (H‐R)‐induced contractile dysfunction of cardiomyocytes. Isolated cardiomyocytes were subjected to 3 min. of hypoxia and 20 min. of reoxygenation in the presence or absence of the inhibitor cocktails. Contractility of cardiomyocytes was expressed as myocyte peak shortening. Inhibition of MMP‐2 by Doxy (25–100 μM), MLCK by ML‐7 (0.5–5 μM) and NOS by L‐NAME (25–100 μM) or 1400W (25–100 μM) protected myocyte contractility after H‐R in a concentration‐dependent manner. Inhibition of these activities resulted in full recovery of cardiomyocyte contractility after H‐R at the level of highest single‐drug concentration. The combination of subthreshold concentrations of NOS, MMP‐2 and MLCK inhibitors fully protected cardiomyocyte contractility and MLC1 from degradation by MMP‐2. The observed protection with addition of L‐NAME or 1400W was better than previously reported combination of ML‐7 and Doxy. The results of this study suggest that addition of NOS inhibitor to the mixture of inhibitors is better strategy for protecting cardiomyocyte contractility.